Supply Chain Performance of Customer and Supplier Relationship on Indian Retail Sector - R, Divyaranjani (International Journal of Supply Chain Management, 2018)
There is a continuous challenge for the Organizations to re-design the Supply Chain for competitive performance. Customer and Supplier Coordination play a vital role in facilitating this process. The present article investigates the effects of Customer and Supplier Coordination on Supply chain performance in Indian Retail Industry. Supply Chain Performance is taken as a composite construct of product quality, product innovation, product flexibility and Product Delivery. The Coordination Theory is used to formulate the conceptual model, and two sets of related Hypothesis are tested using statistical analysis. Survey Method is used to collect the data from Logistics and Supply Chain Managers from Retail Organizations operating in India. The Results have indicated key Coordination areas to improve competitiveness in Indian Retail Sector